Europe-Asia Development Cooperation - Nowik, Marcin (Europejsko-Azjatycka współpraca w obszarze rozwoju, 2010)
The basic aim of the article is to discuss the issue of development cooperation between European Community and Asian countries, to indicate areas of the cooperation, institutions involved, past and present activities in that field. Europe, claiming to be the world's largest ODA donor, implements its world-wide policies in terms of economic cooperation, promotion of democracy and good governance as well as environmental issues also refer to development assistance in Asia. When considering European approach to Asian countries in terms of development assistance, it is necessary to identify two groups of states: Asia and Central Asia. Although being internally diverse, they have some common factors and indicators allowing particular countries to be grouped together. For each region different strategy was adopted and different actions are being implemented to meet particular needs.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 61-70
Keywords: European Union; aid; assistance; development; DCI